LANGKAH CERDAS MEMBANGUN BISNIS HALAL DAN LEGAL : STUDI KELAYAKAN BISNIS MELALUI PENDAFTARAN OSS DAN SERTIFIKASI HALAL - Hazmatul Khumairo', Hazmatul Khumairo'; Rohman, Abdur (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
In the era of the growing halal industry, compliance with legal and halal-certified business regulations is the main key in building a sustainable business. This study aims to analyze strategic steps in building a halal and legal business through business feasibility studies, registration through the Online Single Submission (OSS) system, and the halal certification process. The research method used is a qua litative approach with literature studies and policy analysis related to business licensing regulations and halal certification in Indonesia. The results showed that OSS registration provides convenience in obtaining business licenses quickly and transparently, while halal certification from the Halal Product Guarantee Agency (BPJPH) is an important factor in increasing Muslim consumer confidence. The combination of business legality and product halal assurance is a major factor in increasing business competitiveness in the domestic and global markets. Therefore, business actors are advised to understand the licensing mechanism through OSS and meet halal standards so that businesses can develop optimally and sustainably.